Perception of people with type 2 diabetes mellitus concerning an educational health process - Aliny Lima Santos; Hellen Pollyanna Mantello Cecílio; Sonia Silva Marcon (Rev Rene, 2015)
Objective: to understand the perception of people with type 2 diabetes mellitus about the participation in an educational health process. Methods: qualitative study, conducted with 26 people with diabetes enrolled in the Association for Diabetics. There were 12 meetings entitled “reflective-educational process”, based on the theoretical and methodological strategy of the Culture Circles. Meetings were recorded, transcribed and analyzed according to identification of generative themes and extreme situations. Results: two thematic units emerged: Being in group: space for embracement and construction of knowledge; and Realizing changes resulting from being in a group. Participatory meetings proved to be efficient, as they were configured as support network, space for motivation, construction of knowledge about the disease, living with it, and approximation between professionals and individuals. Conclusion: health education with participatory approach was perceived as satisfactory, favoring living with the disease and changing habits.